Case Report: Contrasting BCL2 Upregulation With Venetoclax in a Case of Refractory Lymphomatoid Papulosis and Progressive Chronic Lymphocytic Leukemia - Guarente, Valerio; Martino, Giovanni; Dorillo, Erica; De Falco, Filomena; Rompietti, Chiara; Sorcini, Daniele; Brogna, Mariangela; Cardinali, Valeria; Ascani, Stefano; Marra, Andrea; Sportoletti, Paolo (Frontiers in Oncology, 2021)
A 57-year-old man affected by high-risk progressive chronic lymphocytic leukemia (CLL), primary resistant to first-line chemoimmunotherapy, developed a type A lymphomatoid papulosis (LyP), during a second progression of CLL. The two blood tumor entities were clonally unrelated. LyP presented with a diffuse (>90% body surface area) cutaneous rash, and was characterized by intensely pruriginous dusky nodules (n=10) and red flat-topped papules (n=60). No response to topical corticosteroids and PUVA phototherapy was observed. In order to effectively treat progressive TP53-mutated CLL, the potent BCL2 inhibitor, venetoclax was initiated with no treatment-related complications. While CLL only achieved a partial response, a complete remission of LyP-associated cutaneous rash and of the intractable pruritus was obtained within 2 months from venetoclax initiation. BCL2 immunostaining of the original cutaneous specimen showed a strong over-expression of the anti-apoptotic protein, restricted to CD30+ lymphoid cells and reactive microenvironment. At 12 months follow-up, the patient is still in complete remission of LyP. Our findings underline the probable pathogenic role of BCL2 in LyP, and the potential therapeutic efficacy of venetoclax for the treatment of this primary cutaneous CD30+ lymphoproliferative disorder, especially in the setting of severe and refractory disease.